2016
DOI: 10.1016/j.radonc.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences regarding prophylactic cranial irradiation: A discrete choice experiment

Abstract: Introduction:In patients with Non-small cell lung cancer (NSCLC) treated with chemoradiotherapy (CRT), prophylactic cranial irradiation (PCI) is not standard practice. This study determined patient preferences for PCI with respect to survival benefit, reduction in brain metastases (BM) and acceptable toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…A recent report also indicates that the likelihood that patients will opt for PCI is dependent on the anticipated magnitude of the reduction in brain metastasis risk, making our data relevant to individualized patient decision-making. [18]…”
Section: Discussionmentioning
confidence: 99%
“…A recent report also indicates that the likelihood that patients will opt for PCI is dependent on the anticipated magnitude of the reduction in brain metastasis risk, making our data relevant to individualized patient decision-making. [18]…”
Section: Discussionmentioning
confidence: 99%
“…Economic dependency status in a family may have an impact on the importance of survival, but education level and annual income are possible confounders, making it difficult to determine the primary factor. Education level has been noted to affect preferences in several lung cancer studies ( Muhlbacher and Bethge 2015 ; Lehman et al, 2016 ). Concerning preferences for cost attributes such as drug prices, it would be appropriate to include annual income rather than education level, considering the strength of the correlation.…”
Section: Discussionmentioning
confidence: 99%
“…A discrete choice experiment by Lehman et al found that 50% of patients with NSCLC, when making hypothetical choices regarding PCI, would accept PCI for no survival advantage long as there was no change in memory or ability to self-care (33). They also found that 90% of patients would accept PCI for a survival benefit of more than 6 months; 52% of patients pre-treatment (78% post-treatment) would have accepted PCI with no survival benefit but for a reduction in BM.…”
Section: Discussionmentioning
confidence: 99%